Pencegahan Hipertensi Pada Remaja Melalui Pendidikan Kesehatan, Inovasi Media Edukasi Interaktif dan Pelibatan Agen Sehat di SMPN 1 Kupang Timur - Grouse Oematan; Marselinus Laga Nur; Anna Talahatu; Inggit Meliana Anggarini; Utma Aspatria (GOTAVA, 2025)
Hypertension is a medical condition in which an individual experiences a persistent increase in blood pressure above the normal threshold, defined as a systolic pressure ≥140 mmHg and/or diastolic pressure ≥90 mmHg. Hypertension, commonly referred to as high blood pressure, is a major risk factor for heart disease, stroke, kidney failure, and various other health complications. This community engagement program aimed to improve knowledge, awareness, and preventive behaviors regarding hypertension among adolescents through health education, innovative interactive educational media, and the involvement of peer health agents at SMPN 1 Kupang Timur. The activities was conducted through several stages, including an initial survey, health education using booklets and interactive websites, and the training of peer health agents from the student council (OSIS). Evaluation results showed a significant improvement: among the 50 participating students, the average score for hypertension knowledge increased from 61.5 to 80.5, with 44 students (88%) showing improvement. Knowledge as a peer health agent rose from 55.7 to 84.8 (92%), and the ability to educate peers saw the most significant jump, from 30.3 to 89.9 (98%) after the intervention. These findings confirm that interactive media and peer education-based approaches are effective in promoting behavioral change and sustainable hypertension prevention within the school environment. This program offers valuable implications for developing similar initiatives in other schools to reduce the incidence of hypertension among adolescents.